ANTIMICROBIAL USE, PRESCRIBING, AND RESISTANCE IN SELECTED TEN SELECTED DEVELOPING COUNTRIES: A BRIEF OVERVIEW - Haque, Mainul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The widespread accessibility of antimicrobials transformed the path of olden times. Many infections beforehand not curable found treatment, forexample, tuberculosis. Scientist, common people thought once that humankind has able conquered microbial diseases. Nonetheless, irrational andunnecessary use antimicrobials create resistant microbes throughout the universe. Moreover, the development new antimicrobials have slowed down,particularly for those diseases of developing countries who have very poor financial ability to pay the research overhead of the inventor. Thereafter,currently available antimicrobials antimicrobials are loosing their efficacy and spectrum everyday against resistant microbes. Subsequently, oncethose diseases were treatable with no antimicrobials or very low profile agents now need the higher form of antimicrobials even multiple agents. Assuch health care cost is increasing every day which is beyond the economic ability of common people of anywhere of the world. All these 10 developingcountries very frequently were observed that overuse and irrational use of antimicrobials. Researchers of these developing countries opined thatanswer remains in continuing medical education for all health-related stakeholders and appropriate policy to stop irrational prescribing, and promoteprudent and rational prescribing and use of medicine, including antimicrobials.